EPOXY HOÁ CAO SU THIÊN NHIÊN LỎNG CÓ NHÓM HYĐROXYL CUỐI MẠCH BẰNG AXIT 3-CLO PERBENZOIC - Giang, Lê Đức; Lý, Phạm Hữu (Vietnam Journal of Science and Technology, 2012)
EPOXIDATION OF HYDROXYL-TERMINATED LIQUID NATURAL RUBBER BY 3-CHLOROPERBENZOIC ACID The epoxidation reaction of hydroxyl-terminated liquid natural rubber ( 4510) by 3-chloroperbenzoic acid in dichloromethane at 250C was studied. The FTIR, 13C- NMR, 1H-NMR and DEPT spectra show that epoxidized liquid natural rubber ( 4560¸4880) has been formed.